Dorsal scapular nerve entrapment neuropathy managed by ultrasound-guided hydrodissection – a case report - Sharma Gaurav Kant; Botchu Rajesh (Journal of Ultrasonography, 2021)
There are myriad causes for upper thoracic and interscapular pain which include pathologies involving the thoracic spine, costovertebral joints, facet joints and muscles (rhomboids and levator scapulae). Dorsal scapular nerve entrapment and the resulting neuropathy is a rare case of upper thoracic and medial scapular pain. The symptoms of dorsal scapular nerve entrapment neuropathy can be similar to other pathologies mentioned above. We report a rare case of dorsal scapular nerve entrapment managed successfully by ultrasound-guided hydrodissection, and describe the technique for the same. Awareness of this rare entity is advised while evaluating upper thoracic and interscapular pain.